Penggunaan Tes Uraian Dalam Mereduksi Perilaku Mencontek Pada Pembelajaran PAI - Eka Widyanti; Nur Fadillah Indah Syari (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2023)
The use of essay tests is a solution that can be done by a teacher in reducing cheating behaviour in Islamic religious education and morals subjects. The focus of the problem in this study is whether the use of essay tests can reduce students' cheating behaviour in class XI IPA 2 at SMA Negeri 1 Sangatta Selatan. The method used in this research is a class action research method by adopting the Kemmis and Taggart Spiral models. The purpose of this study was to determine the reduction of students' cheating behaviour through the use of an essay test in class XI IPA 2 SMA Negeri 1 Sangatta Selatan. The results showed that when viewed from a comparison of the cheating behaviour of XI IPA 2 students, the percentage of cheating behaviour in cycle 1 was 83% and decreased in cycle 2 by 33%, it can be said that the use of an essay test can reduce students' cheating behaviour in Islamic religious education subjects and manners of class XI IPA 2 SMAN 1 South Sangatta. Thus, learning by giving assignments based on descriptive tests has a significant impact on reducing or reducing students' cheating behaviour.